Making 'meanwhile. . .': representing queer African youth through spontaneous collaborative graphic autoethnography. (April 2023) - Meer, Talia; Müller, Alex
We present a participatory creative research project about the embodied experience of queer African youth, which brought together queer young people, academics and artists from Southern and East Africa (as the Qintu Collab) to produce popular media. We describe objectives and process and argue that this work can best be understood as collaborative graphic autoethnography. By working together, the Collab produced the anthology Meanwhile. . .: Graphic Short Stories About Everyday Queer Life in Southern and East Africa, that challenges dominant representations of African queerness, including pathologising public health discourses and heteronationalist political propaganda. This work also dialogically generated socially experienced embodied knowledge about the wellbeing, relationships, fears and aspirations of young queer people. Such collaboration pushes the boundaries of collaborative, autoethnographic and visual methods. Examining our experience shows the co-constructed nature of knowledge and reveals the considerable power of comics as analytical texts, and as basis for further analysis.